Implementation of the STAD Cooperative Learning Model to Improve Indonesian Language Learning Outcomes in Elementary School - Suranto; Zalukhu, Indah Mawati (ETERNAL (English Teaching Journal), 2025)
Indonesian language learning at the elementary school level faces challenges in engaging students and improving learning outcomes. This study aims to enhance Indonesian language learning outcomes in fourth-grade students at SD Lafau Fadorozai through the implementation of the STAD (Student Teams-Achievement Divisions) cooperative learning model. The study adopts a Classroom Action Research (CAR) design involving a single class as the research subject. Data were collected through observations, learning outcome tests, and questionnaires on student response. The implementation of the STAD cooperative learning model was conducted two cycles, focusing on Indonesian language learning. The research results indicate a significant improvement in students' learning outcomes with average score after the application of the STAD model, as evidenced by an increase in The average post-test score (Mean = X) was significantly higher than the average pre-test score (Mean = Y), with a significant difference (p < 0.05) on learning outcome tests and positive student responses toward cooperative learning. The pre-test score was 63.47 and the post-test 66.53 the increase was 4.82%.  These findings suggest that the STAD cooperative learning model is an effective strategy for improving Indonesian language learning outcomes at the elementary school level. This study underscores the importance of cooperative learning models in enhancing the quality of Indonesian language education at the elementary school level.